2010
DOI: 10.1007/s00500-010-0592-0
|View full text |Cite
|
Sign up to set email alerts
|

A neural network-based multi-agent classifier system with a Bayesian formalism for trust measurement

Abstract: In this paper, a neural network (NN)-based multi-agent classifier system (MACS) utilising the trustnegotiation-communication (TNC) reasoning model is proposed. A novel trust measurement method, based on the combination of Bayesian belief functions, is incorporated into the TNC model. The Fuzzy Min-Max (FMM) NN is used as learning agents in the MACS, and useful modifications of FMM are proposed so that it can be adopted for trust measurement. Besides, an auctioning procedure, based on the sealed bid method, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…To attain the trust measurement, the FMM in the model was used as a learning agent in MAS and tailed by combination with Bayesian formalism. The results in proposed model showed improvement as compared to other tactics [91].…”
Section: (Case 3) Improved Hybridizing Elm Based Multi Agent Systementioning
confidence: 80%
See 3 more Smart Citations
“…To attain the trust measurement, the FMM in the model was used as a learning agent in MAS and tailed by combination with Bayesian formalism. The results in proposed model showed improvement as compared to other tactics [91].…”
Section: (Case 3) Improved Hybridizing Elm Based Multi Agent Systementioning
confidence: 80%
“…Consequently, trust was the strong element related to the FMM agents that enabled the CBS technique to increase the performance of the MAS in the training practice. The result showed that the improvement of the accuracy rates of the individual agents [91].…”
Section: (Case 3) Improved Hybridizing Elm Based Multi Agent Systementioning
confidence: 94%
See 2 more Smart Citations
“…Each agent makes its own complete classification and the best one is chosen. Quteishat and his team have developed a Multi-Agent Classifier system based on the TrustNegotiation-Communication model (Quteishat & al, 2010). The proposed TNC-based MAC system consists of an ensemble of neural network-based classifiers.…”
Section: Related Work Similarities and Originalitymentioning
confidence: 99%